Predictors of patient preference for mode of delivery following an obstetric anal sphincter injury. (August 2019) - Cole, Jennifer; Bulchandani, Supriya
Abstract: Objectives: Patients who sustain an Obstetric Anal Sphincter Injury (OASI) have the opportunity to select an elective caesarean section over a vaginal delivery in subsequent pregnancies. It remains unclear whether there are identifiable factors which predict expectant mothers' choices. The primary aim of our study was to explore this issue further in a consecutive group of patients who had suffered OASI. Study design: Data were retrospectively collected for patients attending a specialist OASIS clinic between July 2016 and February 2018. Information routinely collected in clinical practice was considered including mode of previous delivery, severity of OASI, combined with anal incontinence symptoms and endoanal ultrasound results. Logistic regression analysis was used to explore the relationship between these variables and the preferred mode of delivery. Results: A total of 188 patients were identified of whom 153 had complete data for analysis. Approximately 30% (n = 45) of patients preferred to have a caesarean section in their subsequent pregnancy. Bivariate analysis revealed significant associations between choosing a caesarean section in subsequent pregnancy and individuals with major tears (p = 0.001), high anal incontinence scores (p = 0.001) and defects on endoanal ultrasound (p < 0.001). Logistic regression analysis showed statistically significant associations between Caucasian ethnicity (Odds ratio (OR) 12.6, 95% CI 2.4–69.9) and endoanal ultrasound results (OR 2.3, 95% CI 1.7–3.2) with preference for caesarean section. Conclusion: Our data suggests that emphasis is placed by patients on endoanal ultrasound results when making their decision about mode of delivery in a subsequent pregnancy, suggesting a useful application of this tool. Ethnicity is a strong predictor of choice of delivery after OASI and may be potentially useful in forecasting maternity unit services.